A Computational Study on 3‐Azonia‐, 3‐Phosphonia‐, and 3‐Arsoniaspiro[2.2]pentanes and Related Three‐Membered Heterocycles. Issue 16 (27th August 2014) - Trujillo, Cristina; Sánchez‐Sanz, Goar; Alkorta, Ibon; Elguero, José
Abstract A theoretical study at the ab initio MP2/6‐311++G(d, p) level of theory is carried out to characterize several heterocyclic spiro[2.2]pentane cations with N, P, and As as spiro atoms. The strain and relative stability of the spiropentanes are obtained through isodesmic reactions. Nucleus‐independent chemical shifts (NICS) and 3D NICS isosurfaces show σ‐aromatic characteristics, similar to those found in cyclopropane. The interaction with the Cl− anion, which results in four different stationary structures, is studied and characterized by means of the atoms in molecules methodology, and Cl⋅⋅⋅pnicogen, Cl⋅⋅⋅H, and Cl⋅⋅⋅C interactions are found. The most stable structure in all cases corresponds to opening of one of the three‐membered rings, due to the attack of the Cl atom, and CCl bond formation. Furthermore, the reaction with the 3‐boranuidaspiro[2.2]pentane anion results in the formation of a new compound through cleavage of one ring of both reactants.